Primary clear cell adenocarcinoma of vagina - not associated with diethylstilbestrol exposure - Bhattacharya, Sumanta; Dasgupta, Sujoy; Pramanik, Soumyakanti; Ghosh, Prithwijit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The primary clear cell adenocarcinoma (PCCA) of the vagina and the cervix are commonly associated with in utero exposure to diethylstilbestrol (DES). However, it can occur without DES exposure in utero. Due to rare occurrence, there is paucity of data on the literature on non-DES associated PCCA of the vagina. Here we describe a case of 45 years old woman presented with irregular vaginal bleeding with small nodule in the vagina. The growth was excised and sent for histopathological examination, after which the diagnosis turned out to be a case of PPCA of the vagina. After the diagnosis, definite treatment was planned in the form of hysterectomy and pelvic lymphadenectomy and all structures were free of tumour on histopathological examination. The patient remained disease free on short term follow up. The rarity of the occurrence of such a case of PPCA of vagina in Indian scenario and the uniqueness of it in terms of non-association with DES exposure prompted us to report this case.